Non-coding RNA expression analysis revealed the molecular mechanism of flag leaf heterosis in inter-subspecific hybrid rice - Wang, Mengyao; Wang, Jianbo (Frontiers in Plant Science, 2022)
Heterosis has been used widespreadly in agriculture, but its molecular mechanism is inadequately understood. Plants have a large number of non-coding RNAs (ncRNAs), among them, functional ncRNAs that have been studied widely containing long non-coding RNA (lncRNA) and circular RNA (circRNA) that play a role in varied biological processes, as well as microRNA (miRNA), which can not only regulate the post-transcriptional expression of target genes, but also target lncRNA and circRNA then participate the competing endogenous RNA (ceRNA) regulatory network. However, the influence of these three ncRNAs and their regulatory relationships on heterosis is unknown in rice. In this study, the expression profile of ncRNAs and the ncRNA regulatory network related to heterosis were comprehensively analyzed in inter-subspecific hybrid rice. A total of 867 miRNAs, 3278 lncRNAs and 2521 circRNAs were identified in the hybrid and its parents. Analysis of the global profiles of these three types of ncRNAs indicated that significant differences existed in the distribution and sequence characteristics of the corresponding genes. The numbers of miRNA and lncRNA in hybrid were higher than those in its parents. A total of 784 ncRNAs (169 miRNAs, 573 lncRNAs and 42 circRNAs) showed differentially expressed in the hybrid, and their target/host genes were vital in stress tolerance, growth and development in rice. These discoveries suggested that the expression plasticity of ncRNA has an important role of inter-subspecific hybrid rice heterosis. It is worth mentioning that miRNAs exhibited substantially more variations between hybrid and parents compared with observed variation for lncRNA and circRNA. Non-additive expression ncRNAs and allele-specific expression genes-related ncRNAs in hybrid were provided in this study, and multiple sets of ncRNA regulatory networks closely related to heterosis were obtained. Meanwhile, heterosis related regulatory networks of ceRNA (lncRNA and circRNA) and miRNA were also demonstrated.